The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2003
DOI: 10.1016/s0142-9612(02)00253-3
|View full text |Cite
|
Sign up to set email alerts
|

An ultrasonic pulse-echo technique for monitoring the setting of CaSO4-based bone cement

Abstract: We present a new ultrasonic technique for monitoring the entire setting process of injectable bone cement. The problem with existing standards is their subjectivity. Because of this the results are not comparable between different research groups.A strong advantage with the proposed technique is that it is non-invasive and non-destructive, since no manipulation of the cement sample is needed once the measurement has started. Furthermore, the results are reproducible with small variations.The testing was perfor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
33
1
1

Year Published

2006
2006
2017
2017

Publication Types

Select...
4
2
2

Relationship

1
7

Authors

Journals

citations
Cited by 42 publications
(36 citation statements)
references
References 12 publications
1
33
1
1
Order By: Relevance
“…22,26,27 We believe that setting times by Gillmore needles are still relevant to clinical practice despite this subjectivity, 28 with our antibiotic hemispheres appearing stable enough for implantation at Ti and later. We are concerned with implantation of CSH before adequate curing, as mechanical properties and altered hygroscopic setting expansion 29,30 may contraindicate the implantation of uncured antibiotic-impregnated beads in a confined space.…”
Section: Dojmentioning
confidence: 98%
See 1 more Smart Citation
“…22,26,27 We believe that setting times by Gillmore needles are still relevant to clinical practice despite this subjectivity, 28 with our antibiotic hemispheres appearing stable enough for implantation at Ti and later. We are concerned with implantation of CSH before adequate curing, as mechanical properties and altered hygroscopic setting expansion 29,30 may contraindicate the implantation of uncured antibiotic-impregnated beads in a confined space.…”
Section: Dojmentioning
confidence: 98%
“…However, they are not necessarily kept constant among calcium-based cement setting experiments. 21,22 Here we provide the setting times of 98% pure calcium sulfate hemihydrate into calcium sulfate dihydrate when mixed with four commonly used antimicrobial agents: Vancomycin, cefazolin, tobramycin, and amphotericin B. In this study, we are trying to mimic what occurs in the clinical setting by mixing calcium sulfate in a ratio of one vial antibiotic to 25 gm calcium sulfate hemihydrate.…”
Section: Introductionmentioning
confidence: 99%
“…The idea of both methods is to examine visually the sample surfaces to decide whether the formulation has already set, i.e., if no mark can be seen on the surface after indentation. Besides, the setting process might be monitored in real time by non-destructive methods (the continuous approach), e.g., using pulse-echo ultrasound technique [276,277], isothermal differential scanning calorimetry [198,199,[278][279][280][281][282][283][284] and alternating current (AC) impedance spectroscopy [285]. For example, calorimetry measurements suggested that in Equation (2) the endothermic MCPM dissolution and the highly exothermic β-TCP dissolution occurred simultaneously, followed by the exothermic crystallization of DCPD [282].…”
Section: Setting and Hardeningmentioning
confidence: 99%
“…Hence, by monitoring the evolution of some acoustic properties as a function of the setting time, it should be possible to follow the progress of the reaction. This idea was investigated by Carlson et al [6] and Nilsson et al [7] by monitoring the evolution of the acoustic impedance and the sound velocity using pulse-echo ultrasound. A similar approach based on studying the attenuation of ultrasound was proposed by Viano et al [8] The ultrasonic techniques mentioned above share the benefit over the existing standards in the sense that they provide an objective means of on-line assessment of the progress of the reaction.…”
Section: Introductionmentioning
confidence: 99%